Peran Mindfulness terhadap Resiliensi dalam Menghadapi Krisis di Perusahaan X - Andri Hadiansyah; Siti Rahmawati; Alyssa Olivia Halim; Khansa Nadhifah Dwi Permata (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Corporate crises, such as organizational restructuring and management changes, often create psychological pressure that challenges employees’ ability to adapt and remain productive. One important psychological capacity in this context is resilience. Mindfulness has been widely discussed as a potential factor that supports individuals in managing stress and adversity. This study aims to examine the role of mindfulness in predicting employee resilience during a corporate crisis. A quantitative correlational design with a cross-sectional survey approach was employed. Data were collected from employees of Company X using the Mindful Attention Awareness Scale (MAAS) and the Connor-Davidson Resilience Scale (CD-RISC-25). Simple linear regression analysis was conducted to test the proposed hypothesis. The results indicate that mindfulness has a positive and statistically significant effect on resilience (p = 0.01). However, the contribution of mindfulness to resilience is relatively modest, accounting for 4.8% of the variance. These findings suggest that while mindfulness plays a meaningful role in enhancing employee resilience during crisis situations, resilience is also influenced by other organizational and individual factors.